2018
DOI: 10.1021/acs.joc.8b02178
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Cyclopropenes-Involved Carbonylative Carbocyclization Catalyzed by Rh(I) Catalyst: A DFT Study

Abstract: Computational studies were carried out to provide mechanistic insights into the Rh­(I)-catalyzed activation of cyclopropenes and the detailed mechanistic pathways of [3+2+1] carbonylative carbocyclization of tethered ene- and yne-cyclopropenes. Computational results suggest that it is more favorable for the cyclopropene moiety of tethered ene-cyclopropenes to initially undergo heterolytic cleavage of a C–C σ-bond to form a vinyl Rh­(I) carbenoid intermediate than to proceed through homolytic C–C σ-bond cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Subsequent computational studies indicated the need to consider the participation of a rhodium carbene intermediate generated from cyclopropene σ-C−C bond cleavage. 174 Noticeably, the reaction with cyclopropene-ene derivatives was also included in this work, leading in this case to structurally related bicyclic ketones.…”
Section: Metal-catalyzed Ring-opening Reactions Of Cyclopropenes With...mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent computational studies indicated the need to consider the participation of a rhodium carbene intermediate generated from cyclopropene σ-C−C bond cleavage. 174 Noticeably, the reaction with cyclopropene-ene derivatives was also included in this work, leading in this case to structurally related bicyclic ketones.…”
Section: Metal-catalyzed Ring-opening Reactions Of Cyclopropenes With...mentioning
confidence: 99%
“…276,277 In recent years, Wang and co-workers studied the reactivity of 1,n-cyclopropene-enes and -ynes in the presence of CO in the context of rhodium-catalyzed carbonylative cycloisomerization reactions of enynes (see Section 7, Scheme 37B). 174 Interestingly, 3-(amidomethyl)-and similar cyclopropenes 401 showing the C−C double bond of cyclopropene as single unsaturated moiety, also underwent rhodium-catalyzed carbonylation reactions providing cyclobutenone derivatives 402 (Scheme 61). 278 This transformation comprises a regioselective insertion of CO into a σ-C−C bond of the starting cyclopropene.…”
Section: Co Insertion Reactions Into Cyclopropenes Via C−c Bond Cleav...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodium salts coordinated with proper ligands have been reported to be able to realize the activation of CO and H 2 and thus might achieve the reductive carbonylation of aryl iodides to afford aromatic aldehydes [37][38][39][40]. Rh salts generally play vital roles in the catalytic results.…”
Section: Effects Of Rh Speciesmentioning
confidence: 99%
“…[15a] The mechanisms of gold(I)-catalyzed rearrangement of cyclopropenes were also investigated by computational studies. [16] In continuing our research interest on the mechanistic studies of highly strained molecules involved reactions, [17] herein, computational studies were carried out to explore the mechanisms of Rh(I)-and Rh 2 (II)-catalyzed regio-selective transformation of allylic cyclopropenecarboxylates (1) to produce Δ β,γ butenolides 2 and 3, respectively. The different mechanisms for the Rh(I) and Rh 2 (II)-catalyzed ring-opening of 1 are disclosed and the origins of the different regioselectivities are revealed in this work.…”
Section: Introductionmentioning
confidence: 99%